Growth and enzyme activity of wheat under varying levels of cadmium and iron - Adhikari, Tapan (Bangladesh Journal of Botany, 2023)
Effects of cadmium (Cd) and iron (Fe) on growth of Atir and Negev varieties of wheat in solution culture experiment was investigated. Based on Geochem-PC model, four different combinations of pCd (-log free Cd +2 activity) such as (0, 7.9, 8.2 and 8.5) and two levels of pFe (-log free Fe+2 activity) such as (17.0 and 17.6) were formulated as experimental treatments. Shoot dry matter yield of wheat cultivars viz. Atir and Negev were reduced to 80 and 74% at 7.9 pCd level. Atir was the most sensitive genotype for the rate of phytometallophore (PM) release. Alterations in superoxide dismutase (SOD) and peroxidase (POD) enzyme activities were initiated from lower pCd level for both the varieties. Bangladesh J. Bot. 52(3): 755-761, 2023 (September)